Prototipo de vivienda soberana para afrontar el cambio climático arquitectura sostenible la vivienda como ente de consumo a fuente de provisión urbana de recursos y energía. (2022)
This is an architectural project designed to face the two most important realities that relate climate change and the residential sector, on the one hand, housing as part of the problem being and understanding with the environment as an entity of consumption and production of waste and On the other hand, housing as an infrastructure that is not very resilient, is not prepared for the direct and indirect effects of the environmental crisis. Based on these two current characteristics, the proposal is implemented in San Andrés de Tumaco, a territory with complex social and cultural dynamics, where these two aspects would have a high impact.